Event-related neuronal responses to acoustic novelty in single-sided deaf cochlear implant users: Initial findings. Issue 1 (January 2018) - Bönitz, Hanna; Kopp, Bruno; Büchner, Andreas; Lunner, Thomas; Lyxell, Björn; Finke, Mareike
Highlights: Neuronal sound processing was investigated in single-sided deaf cochlear implant (CI) users with a three-stimulus oddball paradigm. Auditory processing differs in sensory and higher order processing between the normal hearing and the CI ear. CI degeneration attenuates early, but not late Novelty-P3 amplitudes. Abstract: Objective: A cochlear implant (CI) is an auditory prosthesis restoring profound hearing loss. However, CI-transmitted sounds are degraded compared to normal acoustic hearing. We investigated cortical responses related to CI-degraded against acoustic listening. Methods: Event-related potentials (ERPs) were recorded from eight single-sided deaf CI users who performed a three-stimulus oddball task, separately with their normal hearing ear and CI ear. The oddball tones were occasionally intermitted by novel sounds. ERP responses were compared between electric and acoustic listening for the auditory (N1) and auditory-cognitive (Novelty P3, Target-P3) ERP components. Results: CI-degraded listening was associated with attenuated sensory processing (N1) and with attenuated early cortical responses to acoustic novelty whereas the late cortical responses to acoustic novelty and the target-P3 did not differ between NH and CI ears. Conclusion: The present study replicates the CI-attenuation of Novelty-P3 amplitudes in a within-subject comparison. Further, we show that the CI-attenuation of Novelty-P3 amplitudes extends to early cortical responses to acoustic novelty, but not to late novelty responses. Significance: The dissociation into CI-attenuated P3 early Novelty-P3 amplitudes and CI-unaffected late Novelty-P3 amplitudes represents a cortical fingerprint of CI-degraded listening. It further contributes to general claims of distinct auditory Novelty-P3 sub-components.